Activation of Autophagy Contributes to Sevoflurane-Induced Neurotoxicity in Fetal Rats - Li, Xingyue; Wu, Ziyi; Zhang, Yi; Xu, Ying; Han, Guang; Zhao, Ping (Frontiers in Molecular Neuroscience, 2017)
Numerous animal studies have demonstrated that commonly-used general anesthetics may result in cognitive impairment in the immature brain. The prevailing theory is that general anesthetics could induce developmental neurotoxicity via enhanced apoptosis. In addition, inhibited proliferation induced by anesthetics has also been reported. So far, whether autophagy, a well-conserved cellular process that is critical for cell fate, also participates in anesthesia-induced neurotoxicity remains elusive. Here, we first examined autophagy-related changes after sevoflurane exposure and the effect of autophagy on apoptosis and proliferation, and we also explored the underlying mechanisms of autophagy activation. Pregnant rats were exposed to 2% or 3.5% sevoflurane for 2 hours on gestational day 14 (G14); then, markers of autophagy and expression of autophagy pathway components were measured in fetal brains 2 hours, 12 hours, 24 hours, 48 hours after anesthesia. Changes in neural stem cell (NSC) apoptosis, neurogenesis, neuron quantity and learning and memory function were examined after administration of an autophagy or PTEN inhibitor. The expression of microtubule-associated protein 1 light chain 3 (LC3)-Ⅱ, Beclin-1 and phosphatase and tensin homolog on chromosome 10 (PTEN) were increased in the 3.5% sevoflurane group, while Sequestosome 1 (P62/SQSTM1), phospho-protein kinase B/protein kinase B (p-Akt/Akt) and mammalian target of rapamycin (mTOR) were decreased. 3-methyladenine (3-MA), an inhibitor of autophagy, or dipotassium bisperoxo-(5-hydroxypyridine-2-carboxyl)-oxovanadate (V) (bpV), a PTEN inhibitor, significantly attenuated the activation of autophagy, reversed the decreased expression of B-cell lymphoma-2 (Bcl-2) and reduced the number of terminal-deoxynucleoitidyl transferase mediated nick end labeling (TUNEL) positive cells, ameliorated the decline of Nestin expression, Ki67 positive cell rate, neuron quantity and cross platform times, and shortened the prolonged escape latency. Our results demonstrated that 2 hours 3.5% sevoflurane exposure at G14 induced excessive autophagy in the fetal brain via the PTEN/Akt/mTOR pathway. Autophagy inhibition reversed anesthesia-induced neural stem cell apoptosis, proliferation decline and memory deficits.